Interação entre os polimorfismos dos genes das citocinas TNF-, IL6, IL10 e BDNF e os efeitos do exercício físico em idosas - Daniele Sirineu Pereira (2012)
Aging is associated with a chronic low-grade inflammatory process with an elevation of the production of inflammatory mediators. High levels of these biological markers are predictors for muscle function and physical performance deterioration in the elderly. Even though physical activity can mitigate the chronic inflammatory process related to aging, there is no consensus neither on the exercise modality nor on the parameters that would be the most appropriate to influence these mediators. Aging is also related to a reduction on neutrotrophic levels that could increase the risk for depression in the elderly. Studies report a significant reduction on levels of the brain-derived neurotrophic factor (BDNF) in depressed elderly. Physical activity has positive effects on depression and induces an elevation on BDNF levels. However, little is known about its pattern of production in response to exercise in the elderly. Functional genetic variations, named single nucleotide polymorphism, may lead to differences in the synthesis and production of inflammatory mediators. The general aim of this thesis was to compare the effect of two physical activity regimen, muscle strengthening exercise and aerobic exercise, in plasma levels of BDNF, soluble tumor necrosis factor alpha (TNF-) receptors, interleukin-6 (IL6), interleukin-10 (IL-10) and in physical performance; to investigate the occurrence of an interaction between TNF- rs1800629, IL6 rs1800795, IL10 rs1800896, and BDNF rs6265 and rs4923463 genes polymorphisms and the effect of physical activity in elderly women. We performed a clinical trial, registered on the Brazilian Register of Clinical Trials -Registro Brasileiro de Ensaios Clinicos (ReBEC: RBR9v9cwf), in which 451 community-dwelling older women were enrolled (71.03 ± 4.8 anos). BDNF and inflammatory mediators were measure by the ELISA (enzyme-linked immunosorbent assay) method; SNP genotyping was performed by the TaqMan method (Applied Biosystems, Foster City, CA); and physical performance by the Timed Up and Go (TUG), 5-chair sit to stand from a chair, and 10-meter walk (10MWT) tests. TheGeriatric Depression Scale was selected as an instrument to screen for depressive disorders. Aerobic capacity was assessed by the 6-minute walk (6MWT) and the Shuttle Walking tests; lower limbs muscle strength, by an isokinetic dinamometer (Biodex Medical Systems Inc, USA). Two physical activity protocols were performed three times a week for ten weeks, 30 sessions in total: muscle strengthening exercise (SE) and aerobic exercise (AE). Results were shown in four different studies. In the first study we investigated the impact of both SE and AE regimen over the BDNF levels and depressive symptoms. There was a significant increase in BDNF levels only for the SE group (F= 17.63, p = 0.001) and a reduction on depressive symptoms for both groups (p = 0.001). BDNF dosages did not correlate with the decrease of depressive symptoms in response to training. The second study aimed to assess the effect of SE and AE protocols on plasma levels of the inflammatory mediators TNFR1, sTNFR2, IL-6 e IL-10, and on performance in 6MWT and muscle strength. The SE regimen significantly reduced sTNFR1 and sTNFR2 levels (F = 4.58, p = 0.033), but not the IL-6 (F = 0.96; p = 0.326) nor the IL-10 (F = 1.87, p = 0.172) cytokine levels. No significant changes were seen on the inflammatory mediators in response to AE (p > 0.05). A significant increase in muscle strength happened for the SE (p = 0.001) and an increase in the walked distance in the 6MWT for the AE protocol (p = 0.001). In the third study we analyzed the effect of plasma levels of the soluble TNF- receptors, IL-6 and IL10 on the physical performance changes after the intervention. Both exercise regimens promoted a significant increase in TUG (F = 149.8, p = 0,001); 5-chair sit to stand from a chair (F = 151.7, p = 0. 001); and 10MWT (F = 63.7, p = 0.001) performances. Baseline plasma levels of the inflammatory mediators did not have an influence on the observed effects for physical performance, regardless of the performed exercise modality (p > 0.05). Despite the reduction in sTNFR1 and sTNFR2 levels in the SE, this outcome did not influence the performance of the participants in the functional tests. Finally, we investigated the interaction between the SNPs of TNF-, IL-6 e IL-10 cytokines and the effect of exercise in the fourth study. A significant interaction between the -308 SNP of TNF- gene and the effect of exercise in mobility, assessed by TUG (F = 10.5, p = 0.001) occurred. Likewise, same interaction was observed between the three genotype polymorphisms and the improvement in TUG performance in response to intervention (F = 13.9, p = 0.001). Elderly women who had the combination of genotypes GG of TNF-, CC+CG of IL6 -174 and GG of IL10 -1082 (low production of TNF- and IL-6, high production of IL-10) presented a greater improvement in TUG performance. However, the analyzed SNPs had no influence on the effect of the exercise over the inflammatory parameters. The results of the study demonstrated that both SE and AE protocols were effective intervention to reduce depressive symptoms and physical performance in community-dwelling older women. Still, only the SE regimen promoted an elevation of BDNF levels and a reduction of inflammatory parameters in the studied sample. Elderly women with a combination of genotypes related to an anti-inflammatory profile presented a higher percentage of improvement in functional mobility, regardless of the performed exercise modality. These findings give support to the interactive influence of genetic and environmental factors, such as the practice of physical activity, contributing to improve physical performance in elderly women.